Bridging the gap between attitudes and action: A qualitative exploration of clinician and exercise professional's perceptions to increase opportunities for exercise counselling and referral in cancer care. Issue 7 (July 2022) - Caperchione, Cristina M.; Sharp, Paul; Phillips, Jane L.; Agar, Meera; Liauw, Winston; Harris, Carole A.; Marin, Elizabeth; McCullough, Susan; Lilian, Ruth
Highlights: Regular exercise is safe for patients and recommended throughout cancer care. Clinicians and exercise professionals face barriers to promoting exercise among cancer patients. Early oncologist exercise recommendations may aid in exercise adherence. Exercise professional -initiated referral follow-up reduces clinician and patient barriers. Multi-disciplinary collaboration is needed to promote exercise throughout care. Abstract: Objective: This study aimed to 1) understand factors impacting the implementation of exercise communication and referral, and 2) explore integrated clinical approaches to exercise communication and referral in cancer care. Methods: Seven focus groups (N = 53) were conducted with clinicians and exercise professionals throughout Sydney, Australia. A sub-sample of participants (n = 9) attended a half-day workshop to identifying best practice approaches for moving forward. Data were analysed using thematic content analysis. Results: Two themes emerged: 1) Factors impacting the knowledge-to-action gap, inclusive of limited exercise specific knowledge and training opportunities, funding structure, and current referral process, and 2) Recommendations for a consistent and efficient way forward, detailing the need for oncologist-initiated communication, distribution of cancer-exercise resources, and access to exercise professionals with cancer expertise. Conclusions: This study identified factors (e.g., cancer-exercise specific training, integration of exercise physiologists) influencing exercise counselling and referral. A potential implementation-referral approach accounting for these factors and how to incorporate exercise into a standard model of cancer care, is described. Future testing is required to determine feasibility and practicality of these approaches. Practical Implications: A pragmatic model is provided to guide implementation-referral, inclusive of oncologist-initiated communication exchange, relevant resources, and access to exercise professionals with cancer expertise.